The socioeconomic geography of organic agriculture in the United States. Issue 9 (26th November 2017) - Kuo, Hui-Ju; Peters, David J
ABSTRACT: To better understand the spatial pattern of organic agriculture in the United States, this research investigates multiple measures of organic farming and examines its environmental and socioeconomic correlates at the meso-level between 2007 and 2012. Drawing data from the Census of Agriculture, the organic index indicates that organic farming is primarily located in New England, along the Pacific Coast, the Northern Great Lakes, and the Western Mountains. Although neighborhood effects did play an important role in organic conversion, a small number of organic intensive counties are expanding in areas that are dominated by conventional agriculture. The regional differences of organic agriculture are associated with ecological factors such as climate and topography. Organic intensive areas tend to have more diverse farm operations, with more women operators and direct sales to people and the community. However, the results show mixed support linking organic production with better socioeconomic settings. Generally, the agroecology approach, which views agriculture and the food systems as being embedded in landscapes and a broader socio-institutional system, helps interpret the regional variation of organic agriculture. To capture organic heterogeneity, this study suggests that more analytical attention be paid to local socioeconomic contexts and the corresponding community-embedded relations.